September 2022 Placement Ads (The Accounting Review, 2022)
The deadline for free position ads to be included in this section of The Accounting Review is two months prior to the desired publication in the January, March, May, July, September, or November issues. Position ads, which are free with the purchase of a job posting in the AAA Career Center, should provide all relevant information about the available positions and must include contact information or application instructions for interested candidates. For more information on how to purchase a job posting in the Career Center, or for updated, detailed information about the placement listings in this issue, please go to the AAA website at http://aaahq.org and click on “Career Center,” or call our office at 941-921-7747.SANTA CLARA UNIVERSITY, Department of Accounting invites applications for a tenure-track position beginning Fall 2023. The position is for the rank of Assistant Professor, although established candidates with exceptional scholarly achievement may be considered for higher ranks. Candidates in all areas of research and teaching interest, especially those with an interest in teaching data analytics and accounting information systems, are encouraged to apply. Candidates should have completed or nearly completed their Ph.D.s and must demonstrate the capacity to undertake scholarly research publishable in leading journals. Applications must be submitted using the university's online application process at: https://jobs.scu.edu/postings/TBA. Please submit a cover letter, cv, sample of research, evidence of teaching effectiveness, and three letters of recommendation. Applications will be accepted and reviewed until the position is filled. SCU is a private Jesuit university located in Silicon Valley. We provide housing subsidies and competitive summer research support. SCU is an EEO/AA employer.ST. MARY'S UNIVERSITY, Greehey School of Business invites applications for a tenure-track position starting August 1, 2023. Candidates will be considered for appointment at the Assistant or Associate rank. An endowed NuStar Professorship may be available for qualified candidates at the Associate rank or for those at the Assistant rank with established experience and a demonstrated record of excellence in teaching, research, or service. Candidates should hold or be near completion of a Ph.D. or equivalent terminal degree in Accounting from an AACSB-accredited university. Preference will be given to candidates who are able to teach across multiple instructional modalities and demonstrate an interest in and the capacity to conduct quality scholarly research. The successful candidate will be expected to teach in more than one of the following areas including: intermediate accounting, advanced accounting, auditing, accounting information systems and governmental and not-for profit accounting. Applications must be submitted at http://stmarytx.applicantpro.com/jobs/ with the option to upload all supporting documents electronically. Please submit (1) letter of application addressing interest in position, (2) curriculum vita, (3) an unofficial graduate transcript, (4) evidence of teaching effectiveness, and (5) names and contact info of three references. Questions may be directed to Tom Madison, Ph.D., Ed Boyle Professor and Chair of the Accounting Department, email: tmadison@stmarytx.edu. Any offer of employment will be contingent upon successful completion of a clear background check and receipt of official transcripts.NAZARBAYEV UNIVERSITY, Graduate School of Business (NUGSB) invites applications for faculty positions (all ranks) in the area of accounting. We seek candidates with high-quality research achievement or potential and excellent teaching skills. Candidates should have a Ph.D. in the relevant field from an accredited institution. We will consider both highly qualified entry-level candidates and experienced faculty. Application required application materials include a cover letter highlighting the expertise, motivation, and interest in the position; curriculum vitae; copy of a research paper; evidence of successful teaching; and two letters of recommendation. Please submit your application by email to: faculty_hiring_gsb@nu.edu.kzWASHINGTON STATE UNIVERSITY–PULLMAN, Carson College of Business, Department of Accounting is seeking qualified candidates for one full-time, open rank, tenure-track position in Accounting, beginning August 2023. Individuals with interests in all areas of accounting will be considered, with preference given to individuals who are interested in teaching accounting information systems and conducting behavioral research. Candidates at all levels must demonstrate a commitment to furthering an environment of diversity, equity, and inclusion among faculty, students, and the broader university community. The full position announcement can be found online at: https://hrs.wsu.edu/jobs/ (posting R-6171) and includes a list of materials that candidates must upload to be considered for the position. Review of applications will begin July 18th, and will continue until position is filled. Questions should be directed to: Search Committee Chair, Sue Gill, Phone: (509) 335–5633; Email: gills@wsu.edu.THE UNIVERSITY OF TEXAS PERMIAN BASIN, Department of Accounting, Finance & Economics invites applications for full-time tenure-track Assistant/Associate Professor of Accounting with an anticipated appointment beginning Fall 2023. Responsibilities: The position will be filled at a salary based on qualifications and experience. The teaching area desired is Tax and or Financial Accounting; other areas will be considered. A current CPA license is highly preferred. Candidates will be expected to teach at both undergraduate and graduate levels. Required qualifications: (1) Earned terminal degree in Accounting from an AACSB-accredited university, ABD will be considered; (2) demonstrated (or strong potential for) scholarly excellence; and (3) willingness to participate in Accounting Student activities. Preferred qualifications: (1) specialization in Taxation and or Financial Accounting; (2) active CPA license; (3) additional accounting or related licenses or certifications; (4) college-level teaching experience, ideally within the field of accounting; and (5) experience teaching online. Please visit: https://utpb.peopleadmin.com/postings/3734/.